Sistem Crowdsourcing sebagai Pembentuk Ulang Cara Kerja dan Distribusi Karya Desain Grafis - Bangsa, P. Gogor (DeKaVe, 2019)
Abstract.Graphic design developed according to technological developments. Likewise, the way of working and how to disseminate graphic design works is very dependent on technological developments in each age. Graphic design is also a means of communication and plays an important role in marketing the products of industrial products.At the age called the Industrial Revolution 4.0 when digital technology became an integral part of people's lives, graphic design also influenced by this development. Both the way of working and the way to distribute graphic design work experienced a very significant change compared to the previous period of technological development. However, this new system, despite being able to provide several profitable opportunities, still has the opposite side that is not as profitable as the crowdsourcing system.Keywords:graphic design, technology, crowdsourcing system.